Self-Reported Prevalence of Chronic Non-Communicable Diseases in Relation to Socioeconomic and Educational Factors in Colombia: A Community-Based Study in 11 Departments - Paul A. Camacho; Diego Gomez-Arbelaez; Johanna Otero; Silvia González-Gómez; Dora I. Molina; Gregorio Sanchez; Edgar Arcos; Claudia Narvaez; Henry García; Maritza Pérez; Eric Hernandez-Triana; Myriam Duran; et al. (Ubiquity Press, 2020)
Background: Chronic non-communicable diseases are prevalent conditions in developing countries, such as Colombia. Several socioeconomic and educational factors have been associated with these pathologies. However, there is little country-specific information regarding the self-reported prevalence of chronic diseases and their association with the aforementioned factors in Colombia. Objectives: To evaluate the current situation of chronic non-transmissible diseases in Colombia by self-report and to analyze its potential relationship with sociodemographic, economic and educational factors. Methods: This is a cross-sectional baseline sub-analysis from the prospective, standardized collaborative PURE study in Colombia. Participants were recruited between 2005 to 2009, in 11 departments of the country, and included 7,485 subjects of 35 to 70 years old. Questionnaires of self-reported chronic non-communicable diseases, and demographic, socioeconomic and educational variables were applied. Results: Hypertension was the most prevalent chronic condition reported with a prevalence of 22.2% (21.2%-23.1%, 95% CI), followed by diabetes with a prevalence of 5.7% (5.1%-6.2%, 95% CI), asthma 2.7% (2.2%-3.0%, 95% CI), coronary heart disease 2.4% (2.0%-2.7%, 95% CI), stroke and heart failure 1.5% (1.2%-1.8%, 95% CI) each, chronic obstructive pulmonary disease 1.2% (0.6%-1.5%, 95% CI), and cancer 1.2% (1.0%-1.5%, 95% CI). Among the study sample, 23.3% (22.4%-24.3%, 95% CI) reported having one chronic NCDs, and 6.4% (5.9%-7.0%, 95% CI) reported having multiple chronic NCDs. The prevalence of multiple NCDs increased significantly with age, was more common in those from households with higher income, whereas it was significantly lower in persons with high education. The central and central-east regions of the country are those with the higher prevalence of self-reported NCDs. Conclusion: The results of the current study indicate the presence of socioeconomic and educational inequalities in the distribution of chronic NCDs in the Colombian population.